THEORETICAL SUBSTANTIATION OF THE PNEUMOMECHANICS OF THE CZECH GIN FOR THE SEPARATION OF FIBER FROM SEEDS - Abdullayev, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The increase in the mass of the cotton pieces slows down the movement and the speed of movement. This, in turn, has a positive effect on the ginning process. From the graphs of the distance traveled and the speed, it can be seen that the ginning process in the first and second pairs of cylinders is more intense than in the third and fourth pairs of cylinders, i.e. 80% of the ginning occurs in the first and second pairs of cylinders. We can observe this situation by the parabolic law of the graph of the dependence of the distance traveled on time, and the graph of the dependence of the speed on time - by the law of the increasing straight line.